2016
DOI: 10.1016/j.engstruct.2015.12.040
|View full text |Cite
|
Sign up to set email alerts
|

An innovative framework for probabilistic-based structural assessment with an application to existing reinforced concrete structures

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. ABSTRACTA novel framework for probabilistic-based structural assessment of existing structures, which combines model identification and reliability assessment procedures, considering in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…The methodology can also be expanded to consider multiple parameters, which is a common scenario on civil infrastructures [26,27,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology can also be expanded to consider multiple parameters, which is a common scenario on civil infrastructures [26,27,13].…”
Section: Discussionmentioning
confidence: 99%
“…the model is successfully calibrated) when the model parameters θ take the values θ * . Although our example only updates one parameter, the methodology can also consider multiple parameters, which is a common scenario in civil infrastructures [26,27,13].…”
Section: Observation and Numerical Model Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the influence of each model parameter and to reduce the computational cost of the probabilistic analysis, a sensitivity analysis was performed. Thus, for each parameter, an importance measure b k , was obtained (Matos et al 2016), see expression 4:…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Kralik [25] utilized the probability analysis to estimate the containment failure of concrete structures. Matos et al [26] evaluated the behavior of simple beam experimentally and numerically using a linear and nonlinear probability analyses and concluded that the nonlinear probability analysis can be used to estimate the behavior of structures.…”
Section: Shock and Vibrationmentioning
confidence: 99%